Prevalence and reproduction of Tropilaelaps mercedesae and Varroa destructor in concurrently infested Apis mellifera colonies - Ninat Buawangpong (2018)
© 2015, INRA, DIB and Springer-Verlag France. The prevalence of Tropilaelaps mercedesae and Varroa destructor in concurrently infested A. mellifera colonies in Thailand was monitored. We also assessed the fecundity of T. mercedesae and V. destructor in naturally infested brood and in brood cells deliberately infested with both mite genera. Results showed that the natural co-infestation of an individual brood cell by both mite genera was rare (<0.1 %). Overall, T. mercedesae was the more dominant brood parasite of A. mellifera than V. destructor. In naturally infested brood, the proportion of nonreproductive Tropilaelaps (29.8 ± 3.9 %) was lower than that of Varroa (49.6 ± 5.9 %). Both mites produced similar numbers of progeny (T. mercedesae = 1.48 ± 0.05; V. destructor = 1.69 ± 0.14). The two mite genera also reproduced normally when they were deliberately introduced into the same brood cells. In two separate assessments, the average worker brood infestations of T. mercedesae (19.9 %) were significantly higher than that of V. destructor (0.7 %). Our results on the higher prevalence and reproductive ability of T. mercedesae in concurrently infested colonies reaffirm Tropilaelaps’ competitive advantage over V. destructor and their reported negative impact to A. mellifera colonies.